Human Bioclimatic Conditions, Trends, and Variability in the Athens University Campus, Greece - Panagiotis T. Nastos; Andreas Matzarakis (Advances in Meteorology)
The objective of this work is the assessment of human thermal bioclimatic conditions in the Athens University Campus (AUC), including the Faculties and their respective Departments of the largest state institution of higher learning in Greece, and among the largest universities in Europe. The analysis of bioclimate was carried out, using the physiologically equivalent temperature (PET), which is based on the energy balance model of the human body. The meteorological data required for the calculation of PET concern hourly values of air temperature, relative humidity, wind speed and total solar radiation, for the time period 1999–2007. The recorded data sets were obtained from the meteorological station of the Laboratory of Climatology and Atmospheric Environment of the University of Athens. The results revealed the hours of the day in which thermal comfort or stress prevails, as well as the trends and variability of PET, for the studied period. Finally, the intense heat waves occurred during summer 2007 along with extreme cold conditions during December 2003-February 2004 were analyzed in terms of PET classes and compared to the respective average bioclimatic conditions of the study period.